A global multinational survey of cefotaxime-resistant coliforms in urban wastewater treatment plants. (November 2020) - Marano, Roberto B.M.; Fernandes, Telma; Manaia, Célia M.; Nunes, Olga; Morrison, Donald; Berendonk, Thomas U.; Kreuzinger, Norbert; Tenson, Tanel; Corno, Gianluca; Fatta-Kassinos, Despo; Merlin, Christophe; Topp, Edward; et al.
Graphical abstract: Highlights: Cefotaxime-resistant (CTX-R) coliforms in wastewater were surveyed. The survey targeted influents and effluents in 57 WWTPs across five continents. The relative abundance of CTX-R coliforms varied significantly between WWTPs. Some WWTPs discharged high and potentially hazardous levels of CTX-R coliforms. Abstract: The World Health Organization Global Action Plan recommends integrated surveillance programs as crucial strategies for monitoring antibiotic resistance. Although several national surveillance programs are in place for clinical and veterinary settings, no such schemes exist for monitoring antibiotic-resistant bacteria in the environment. In this transnational study, we developed, validated, and tested a low-cost surveillance and easy to implement approach to evaluate antibiotic resistance in wastewater treatment plants (WWTPs) by targeting cefotaxime-resistant (CTX-R) coliforms as indicators. The rationale for this approach was: i) coliform quantification methods are internationally accepted as indicators of fecal contamination in recreational waters and are therefore routinely applied in analytical labs; ii) CTX-R coliforms are clinically relevant, associated with extended-spectrum β-lactamases (ESBLs), and are rare in pristine environments. We analyzed 57 WWTPs in 22 countries across Europe, Asia, Africa, Australia, and North America. CTX-R coliforms were ubiquitous in raw sewage and their relative abundance varied significantly (<0.1% to 38.3%), being positively correlated ( p < 0.001) with regional atmospheric temperatures. Although most WWTPs removed large proportions of CTX-R coliforms, loads over 10 3 colony-forming units per mL were occasionally observed in final effluents. We demonstrate that CTX-R coliform monitoring is a feasible and affordable approach to assess wastewater antibiotic resistance status.